Ambient air pollution and carcinogenic activity at three different urban locations - Ivana Jakovljević; Zdravka Sever Štrukil; Gordana Pehnec; Tajana Horvat; Mandica Sanković; Antun Šumanovac; Silvije Davila; Nikolina Račić; Goran Gajski (Ecotoxicology and Environmental Safety)
Measurements of polycyclic aromatic hydrocarbons (PAHs) were simultaneously carried out at three different urban locations in Croatia (Zagreb, Slavonski Brod and Vinkovci) characterized as urban residential (UR), urban industrial (UI) and urban background (UB), respectively. This was done in order to determine seasonal and spatial variations, estimate dominant pollution sources for each area and estimate the lifetime carcinogenic health risks from atmospheric PAHs. Mass concentrations of PAHs showed seasonal variation with the highest values during the colder period and the lowest concentration during the warmer period of the year. The contribution of four- and five-ring PAHs to the total PAH concentrations was slightly lower during the warmer period of the year at all locations, while the contribution of six-ring PAHs was higher in the warmer period compared to the colder one. Spearman correlation analysis revealed a negative correlation between temperature and PM10 and temperature and PAHs during the cold season, while in the warm period correlation with temperature was negative for PAHs and positive for PM10. Different statistical methods were used to estimate possible dominant pollution sources for each tested area. The obtained results indicated petrogenic and pyrogenic sources, petroleum combustion, and vehicle emission as dominant sources at the UR and UB locations, while vehicle emission, biomass and coal burning, and pyrogenic sources were recognized as dominant sources at the UI location. Cancer risk values obtained during the analysis were at an acceptable limit level, which was between 10−6 and 10−4 (values higher than 10−4 indicate high probable health risks).